2005
DOI: 10.1121/1.2118367
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic modes of vocal tract articulation for American English vowels

Abstract: The purpose of this study was to investigate the spatial similarity of vocal tract shaping patterns across speakers and the similarity of their acoustic effects. Vocal tract area functions for 11 American English vowels were obtained from six speakers, three female and three male, using magnetic resonance imaging (MRI). Each speaker's set of area functions was then decomposed into mean area vectors and representative modes (eigenvectors) using principal components analysis (PCA). Three modes accounted for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…Previously published area functions for eight speakers were used to synthesize vowel samples in the present study ͑Story et al, 1996͑Story et al, , 1998Story, 2005a͒. This included four male ͑range 29-40 years͒ and four female ͑range 23-39 years͒ speakers.…”
Section: Methods a Area Function Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously published area functions for eight speakers were used to synthesize vowel samples in the present study ͑Story et al, 1996͑Story et al, , 1998Story, 2005a͒. This included four male ͑range 29-40 years͒ and four female ͑range 23-39 years͒ speakers.…”
Section: Methods a Area Function Setsmentioning
confidence: 99%
“…These collections of area functions, which are assumed representative of an individual speaker's production of a target vowel or consonant, have then been used in the development of speech production models and speech synthesizers ͑e.g., Ciocea, 1997;Story, 2005aStory, , 2005bMullen et al, 2007͒. The similarity of speech sounds produced by areafunction-based synthesis to natural speech has been typically assessed by comparing calculated formant frequencies to formant frequencies extracted from recorded speech ͑Story et , 1998Story, 2005a͒. Reasonable similarity has been demonstrated; however, stimuli generated based on measured area functions have rarely been evaluated perceptually.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the experiment, each listener participated in a brief training protocol consisting of 16 pairs of simulated vowels that were produced using a kinematic model of the vocal folds (Titze, 1984(Titze, , 2006 coupled to a wave-reflection model of the trachea and vocal tract (Liljencrants, 1985;Story, 2005). These simulated vowels had different extents of modulation (1%, 5%, 10%, 20%), one neutral vowel (/@/), and one f o (either 123 Hz for the male simulations or 247 Hz for the female simulations).…”
Section: Listening Taskmentioning
confidence: 99%
“…Statistical analyses of collections of tongue configurations or complete vocal tract shapes (i.e., area functions) have revealed that a small number of canonical deformation patterns (variously referred to as factors, components, basis functions, or modes) can explain most of the variation in vocal tract shape during vowel production (Harshman et al, 1977;Shirai and Honda, 1977;Jackson, 1988;Johnson et al, 1993;Nix et al, 1996;Story and Titze, 1998;Hoole, 1999;Zheng et al, 2003;Iskarous, 2005;Story, 2005;Mokhtari et al, 2007). These deformation patterns tend to exhibit similarities in shape across speakers and are related to specific formant frequency patterns when superimposed on a mean or neutral vocal tract shape.…”
Section: Introductionmentioning
confidence: 99%